Универсальный измерительный блок для изучения трех фотоэффектов на монохроматоре УМ-2 - Ушаков, В. В.; Корж, Ирина Анатолиевна (НТУ "ХПИ", 2004)
By way of extending of functional mobility and didactic capacity of educational equipment the laboratory device based on monochromator УМ-2 for learning three kinds of photoeffect - external (with vacuume phototube, or photoelectronic multiplyer), internal(with photoresistor) and ventil (with photodiode) is actualized. Alternation brings to effect by adequate commutation of apparatus and elements on the stand. Computation of the optimal duty of ventil photoelement and Plane constant is realized on PC
Keywords: внутренний фотоэффект; внешний фотоэффект; вентильный фотоэффект; фотодиод; вакуумный фотоэлемент; фоторезистор